2020
DOI: 10.1002/pon.5387
|View full text |Cite
|
Sign up to set email alerts
|

Fear of cancer recurrence among survivors of childhood cancer

Abstract: ObjectivesFear of cancer recurrence (FCR) has not been widely explored in survivors of childhood cancer. Yet, childhood survivors are at risk of experiencing late effects and may be especially vulnerable. The aims of the current study were to conduct a retrospective chart review to determine the prevalence and persistence of FCR among survivors of childhood cancer and to examine factors that may be related to FCR.MethodsSurvivors of childhood cancer (n = 228, mean attained age = 14.5 years [range = 4.7‐21 year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
40
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(40 citation statements)
references
References 28 publications
(43 reference statements)
0
40
0
Order By: Relevance
“…Beyond these central findings, this study extends the current literature on fear of cancer recurrence. The two published studies in pediatric samples both use single, unvalidated items to assess fear of recurrence 9,35 . We present the first data using a comprehensive measure of fear of recurrence that is well‐validated in adult populations, although it requires more extensive validation in pediatric populations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Beyond these central findings, this study extends the current literature on fear of cancer recurrence. The two published studies in pediatric samples both use single, unvalidated items to assess fear of recurrence 9,35 . We present the first data using a comprehensive measure of fear of recurrence that is well‐validated in adult populations, although it requires more extensive validation in pediatric populations.…”
Section: Discussionmentioning
confidence: 99%
“…Fear of cancer recurrence, defined as “the fear, worry or concern relating to the possibility that cancer will come back or progress” 8 is among the most prevalent and distressing concerns reported by survivors of all ages 9–11 . Some degree of fear of recurrence is common after cancer.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date and to the best of our knowledge, only two published studies have quantitatively examined FCR in pediatric samples. In the first study, Wroot and colleagues 9 reported that 43% of childhood cancer survivors endorse fear about the possibility of their cancer returning. In a subsequent study, Koutná and colleagues 10 found that FCR was positively associated with both symptoms of post‐traumatic stress and post‐traumatic growth in children.…”
Section: Introductionmentioning
confidence: 99%
“…Further, data suggest that FCR is higher among survivors of childhood cancer than among survivors of adult cancer 4 . In survivors of childhood cancer, higher FCR is associated with a range of difficulties that include impaired psychological functioning, poor health‐related quality of life, greater healthcare utilization, and maladaptive health behaviors 5–8 . There is a critical need for more research on FCR in childhood cancer survivors to guide targeted intervention.…”
Section: Introductionmentioning
confidence: 99%